Cardiac-vascular-respiratory coupling analysis during 6-degree head-down tilt microgravity analogue. (February 2022) - Shankhwar, Vishwajeet; Singh, Dilbag; Deepak, K K
Highlights: HDT microgravity simulation of healthy subjects (n=20) was investigated. Identified the interaction changes among cardiac, vascular and respiratory systems. Interactions were evaluated using coupling indexes based on conditional entropy. HDT increased the effect of vascular on cardiac. Abstract: In the study, quantitative analysis was done to identify the interaction among cardiac, vascular and respiratory signals for 6-degree head-down tilt (HDT) microgravity analogue. This HDT shifts the blood volume towards the thoracic cavity of the human body. The linear and non-linear domain analyses are based on coherence techniques that are used to analyse these cardiovascular responses. But they lack to measure the information flow and coupling changes that occurred during HDT. The present study applied an information domain approach for the investigation of non-linear causality to the heart rate variability, systolic blood pressure and respiration measured during HDT. It was hypothesized that the HDT will demonstrate alteration in cardiac, vascular and respiratory parameters. Twenty healthy subjects were inspected each for 10 min at supine rest and HDT. The responses were significant for cardiac and vascular but not for the respiratory system during HDT. It was observed that during HDT, the parasympathetic nervous system activated and increased the effect of vascular on the cardiac. The effect of respiration on either vascular or cardiac was not significant, therefore the variation and coupling observed in the vascular and cardiac systems are solely because of HDT. The results of this study support the hypothesis and revealed that the HDT altered the autonomic function parameters. It can be concluded that the HDT increases the parasympathetic activity and cardiovascular interaction as well as confirmed the usefulness of conditional entropy for coupling analysis.